Antitumor activity of [Pt(O,O'-acac)(γ-acac)(DMS)] in mouse xenograft model of breast cancer - Muscella, A (Nature Publishing Group, 2014)
The higher and selective cytotoxicity of [Pt(O,O′-acac)(γ-acac)(DMS)] toward cancer cell in both immortalized cell lines and in breast cancer cells in primary cultures, stimulated a pre-clinical study so as to evaluate its therapeutic potential in vivo. The efficacy of [Pt(O,O′-acac)(γ-acac)(DMS)] was assessed using a xenograft model of breast cancer developed by injection of MCF-7 cells in the flank of BALB/c nude mice. Treatment of solid tumor-bearing mice with [Pt(O,O′-acac)(γ-acac)(DMS)] induced up to 50% reduction of tumor mass compared with an average 10% inhibition recorded in cisplatin-treated animals. Thus, chemotherapy with [Pt(O,O′-acac)(γ-acac)(DMS)] was much more effective than cisplatin. We also demonstrated enhanced in vivo pharmacokinetics, biodistribution and tolerability of [Pt(O,O′-acac)(γ-acac)(DMS)] when compared with cisplatin administered in Wistar rats. Pharmacokinetics studies with [Pt(O,O′-acac)(γ-acac)(DMS)] revealed prolonged Pt persistence in systemic blood circulation and decreased nefrotoxicity and hepatotoxicity, major target sites of cisplatin toxicity. Overall, [Pt(O,O′-acac)(γ-acac)(DMS)] turned out to be extremely promising in terms of greater in vivo anticancer activity, reduced nephrotoxicity and acute toxicity compared with cisplatin.